2012
DOI: 10.2169/internalmedicine.51.8081
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly Progressive Glomerulonephritis Associated with PR3-ANCA Positive Subacute Bacterial Endocarditis

Abstract: Patients with bacterial endocarditis often have renal complications. This report presents the case of an elderly man with rapidly progressive glomerulonephritis (RPGN) associated with subacute bacterial endocarditis (SBE) due to Enterococcus faecalis infection. The patient was positive for anti-proteinase 3-antineutrophil cytoplasmic antibody (PR3-ANCA) and rheumatoid factor (RF) with hypocomplementemia. Treatment for SBE with antibiotics and the surgical replacement of the affected valves resulted in an impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 16 publications
1
12
0
1
Order By: Relevance
“…Our literature review, in fact, identified 24 case reports of documented ANCA-positive patients with IE exhibiting renal impairment. 11,24,37,39,40,4245,47,48,50,51,54,5759,61 Twenty-one of these latter patients underwent renal biopsy showing: extracapillary GN with immune deposits (N = 5), pauci-immune GN (N = 4), segmental and focal necrotizing GN (N = 4), endocapillary GN with immune deposits (N = 3), interstitial nephritis (N = 1), chronic sclerotic GN (N = 1), both pauci-immune GN and interstitial nephritis (N = 2), and both endocapillary GN and interstitial nephritis (N = 1). 11,24,37,39,40,4245,47,48,50,51,54,5759,61 Altogether, our data suggest that whether patients with ANCA-associated IE, develop commonly renal impairment, renal damage are nonspecific in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our literature review, in fact, identified 24 case reports of documented ANCA-positive patients with IE exhibiting renal impairment. 11,24,37,39,40,4245,47,48,50,51,54,5759,61 Twenty-one of these latter patients underwent renal biopsy showing: extracapillary GN with immune deposits (N = 5), pauci-immune GN (N = 4), segmental and focal necrotizing GN (N = 4), endocapillary GN with immune deposits (N = 3), interstitial nephritis (N = 1), chronic sclerotic GN (N = 1), both pauci-immune GN and interstitial nephritis (N = 2), and both endocapillary GN and interstitial nephritis (N = 1). 11,24,37,39,40,4245,47,48,50,51,54,5759,61 Altogether, our data suggest that whether patients with ANCA-associated IE, develop commonly renal impairment, renal damage are nonspecific in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…42 Although interpretation of a positive c-ANCA may be difficult, it is likely that hypocomplementemia and the presence of at least one other autoantibody such as RF, ANA, or cryoglobulin are more suggestive of an ANCA-positive bacterial endocarditis rather than an ANCA vasculitis. 46 The patient presented here had hypocomplementemia, a positive RF, and positive c-ANCA titer.…”
Section: Discussionmentioning
confidence: 69%
“…In particular, the presence of c-ANCA is generally thought to be highly specific for GPA. 41 However, c-ANCA directed against PR-3 positivity has also been well documented in infectious endocarditis 4246 and more specifically in Bartonella endocarditis. 3,5,911,26,27,47 The presence of c-ANCA in infectious endocarditis is unclear: it may represent a false-positive or related to the infection or the production of c-ANCA may be induced through B-cell activation after release of PR-3 from neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Literature regarding the appropriate treatment of patients with ANCA positive infectious endocarditis-associated GN is currently not consistent. Some propose treatment with antibiotics alone [10], others propose a combination of antibiotics and steroids [11,[18][19][20] and a third group suggest surgery followed by antibiotics without steroids [21]. Interestingly, in 1998 Haseyama et al [19] proposed that patients with ANCA positive infectious endocarditis-associated GN and low titers of PR3 ANCA (e.g., below 25 IU/ml) can be treated with antibiotics alone, while patients with higher titers of PR3 ANCA antibodies (e.g.…”
Section: Discussionmentioning
confidence: 99%